Certification of Radome Lightning Direct Effects Protection. Issue 1 (January 2021) - Fei, Qin; Ying, Wu
Abstract: Composite material is used more and more in airplanes year after year. The electrical conductivity of composite material structure is poorer than metal structure, so appropriate lightning protection measures should be adopted to shunt lightning current when composite structure suffering lightning strike, and the harmful consequence will be minimized. The paper takes radome as an example, which is located at nose area liable to suffer lightning strike, introduces radome lightning protection measures, and according to lightning direct effect verification process, discusses on means of compliance, plans high voltage strike attachment test and high current physical damage test of radome. It provides reference for airworthiness verification for radome.